2013
DOI: 10.1152/ajpregu.00489.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic effects on sympathetic vasomotor outflow and blood pressure during exercise with inspiratory resistance

Abstract: The purpose of the present study was to clarify the influence of inspiratory resistive breathing during exercise under hypoxic conditions on muscle sympathetic nerve activity (MSNA) and blood pressure (BP). Six healthy males completed this study. The subjects performed a submaximal exercise test using a cycle ergometer in a semirecumbent position under normoxic [inspired oxygen fraction (FiO2) = 0.21] and hypoxic (FiO2 = 0.12-0.13) conditions. The subjects carried out two 10-min exercises at 40% peak oxygen up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 49 publications
7
50
0
Order By: Relevance
“…Additionally, we previously showed that MSNA does increase during mild dynamic exercise in acute hypoxic conditions (Katayama et al . , b ). These results suggest that the cardiopulmonary baroreflex during dynamic exercise could be modified in the presence of heightened sympathetic vasomotor activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, we previously showed that MSNA does increase during mild dynamic exercise in acute hypoxic conditions (Katayama et al . , b ). These results suggest that the cardiopulmonary baroreflex during dynamic exercise could be modified in the presence of heightened sympathetic vasomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…The MSNA bursts were identified from the mean‐voltage neurogram using customized computer program‐assisted inspection (Katayama et al . , b , ), which accounted for the latency from the ECG R wave to the sympathetic burst (Fagius & Wallin, ). The MSNA was quantified as burst frequency (BF, in bursts per minute) and incidence (BI, in bursts per 100 heart beats; Saito et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Respiratory variables were determined by an online system with a mixing chamber, as in our previous studies (Katayama et al . , ). The subjects breathed through a leak‐free nasal mask (5719; Hans Rudolph, Kansas City, MO, USA).…”
Section: Methodsmentioning
confidence: 99%